2019
DOI: 10.2217/pgs-2018-0100
|View full text |Cite
|
Sign up to set email alerts
|

Association between SLCO1B1 rs4149056 and Tegafur–Uracil-Induced Hepatic Dysfunction in Breast Cancer

Abstract: Aim: The aim of this study was to identify pharmacogenomic biomarkers to predict tegafur–uracil (UFT)-induced liver dysfunction. Patients & methods: A total of 68 patients, who were administered UFT, were evaluated using a two-step pharmacogenomics analysis. Results: The first screening revealed the association between five SNPs and UFT-induced hepatic dysfunction. In the second step, SLCO1B1 (rs4149056) was found to be the only SNP associated with UFT treatment-related elevation of aspartate aminotransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A meta-analysis revealed an association between the SLCO1B1 521T>C polymorphism and the risk of statin-induced adverse drug reactions including an abnormal alanine transaminase (ALT) level [23]. Another study including patients with breast cancer receiving tegafur–uracil also showed that patients with the CC or CT genotypes had higher risk of aspartate aminotransferase and ALT level elevation compared to those with the TT genotype [24]. These studies confirmed an association between the SLCO1B1 521T>C polymorphism and drug-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed an association between the SLCO1B1 521T>C polymorphism and the risk of statin-induced adverse drug reactions including an abnormal alanine transaminase (ALT) level [23]. Another study including patients with breast cancer receiving tegafur–uracil also showed that patients with the CC or CT genotypes had higher risk of aspartate aminotransferase and ALT level elevation compared to those with the TT genotype [24]. These studies confirmed an association between the SLCO1B1 521T>C polymorphism and drug-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%